In vitro gas production of fibrous substrates with the inclusion of yeast - Marrero, Yoandra; Ruiz, O.; Corrales, A.; Jay, O.; Galindo, Juana; Castillo, Yamicela; madera, Norma (Cuban Journal of Agricultural Science, 2014)
The in vitro gas production technique was applied for studying the effect of the yeast species and its inclusion dosage on ruminal fermentation of fibrous substrates. Two experiments were executed. In the first, the effect of yeast inclusion of different species on in vitro gas production of star grass (Cynodon nlemfuensis) was determined and in the second, two levels (5 and 10 mg of DM/mL) of the yeast strain showing the best performance in the first experiment were included for confirming its effect on gas production of maize stubble. Controls without yeast and a blank with the non-inoculated culture were included. As result, all strains had a gas production higher than the control, except in that including strain 15. The best performance was in the one in which strain 27 was incorporated. Strains of S. cerevisiae had an intermediate performance regarding the rest. The inclusion of 10 mg DM/mL of the strain 27 (Pichia guillermondii) stimulated in vitro gas production of the maize stubble until 48 h of fermentation. It is concluded that the species and strain of yeasts, as well as their inclusion dosage, have determinant effect on in vitro gas production of different fibrous substrates. This reasserts the importance of selecting the adequate strains for their utilization as additive in diets for ruminants, according to the feed intended to be used. Key words: yeasts, Pichia guillermondii, rumen, gas production